Methylprednisolone prevents bacterial translocation in thioacetamide-induced liver failure in rats - Harputluoğlu, Murat Muhsin Muhip; Temel, İsmail and Demirel, Ulvi and Seçkin, Yüksel and Aladağ, Murat and Otlu, Barış and Karadağ, Neşe and Özyalın, Fatma and Aydoğan, Nilay and Selçuk, Engin Burak (Turkish Journal of Gastroenterology, 2017)
Abstract Background/Aims: Steroids have been shown to prevent intestinal oxidative stress. We investigated the effects of methylprednisolone on intestinal oxidative damage and bacterial translocation in thioacetamide-induced liver failure in rats. Materials and Methods: Group 1 (n=8) was the control group. In group 2 (n=8), the thioacetamide group, rats received 300 mg/kg intraperitoneal thioacetamide daily for 2 days. In group 3 (n=8), the thioacetamide+methylprednisolone group, treatment with methylprednisolone (30 mg/kg intraperitoneal) was commenced 48 h before the first dose of thioacetamide. In group 4 (n=8), the methylprednisolone group, the rats received only methylprednisolone (30 mg/kg intraperitoneal). Results: Serious hepatic and intestinal oxidative damage and high bacterial translocation frequencies were observed in the thioacetamide group compared with those of the controls. Bacterial translocation frequency in the thioacetamide+methylprednisolone group was significantly lower than that in the thioacetamide group (p Conclusion: Our findings suggest that methylprednisolone reduces bacterial translocation by preventing intestinal oxidative damage in this model of acute liver failure in rats. Cite this article as: Harputluoğlu MMM, Temel İ, Demirel U, et al. Methylprednisolone prevents bacterial translocation in thioacetamide-induced liver failure in rats. Turk J Gastroenterol 2017; 28: 394-400.